Effect of Formulation Mixture of Herbicide IPA Glyphosate and Methyl metsulfuron on Ischaemum timorense Weeds - febrianti, cici; ., sarbino; ., astina (Jurnal Sains Pertanian Equator, 2020)
The use of a single herbicide often cannot control all types of weeds. Increase the effects of weed control. This study aims to study the effectiveness of glyphosate and methyl metsulfuron herbicides to control the Ischaemum timorense weed and determine the nature of the mixture. This research was conducted from January to April 2019, for ± 4 months in the greenhouse and Pesticide Laboratory of the Faculty of Agriculture, Tanjungpura University, Pontianak. The research was arranged in random groups. The treatment consisted of 4 types of herbicides with five dose levels and 1 control, namely glyphosate (0, 0.188, 0.375, 0.750, 1.5, 3.0) l / ha, methyl metsulfuron (0, 10, 20, 40, 80, 160) g / ha, herbicide mixture A 240/10 SL (0, 0.25, 0.50, 1.00 2.00, 4.00) l / ha and mixed herbicide B 360/10 SL (0, 0 , 25, 0.50, 1.00, 2.00, 4.00) l / ha. The target weed is Ischaemum timorense, a grass weed which is planted in a 14 cm diameter pot and a target of 3 MST (Three weeks after planting a herbicide test is applied). The variables observed are the level of weed damage that was assessed through phytotoxicity scoring and weed dry weights and analysis of herbicide mixture properties. The results showed that the higher the dose of the herbicide that was given, the more effective the suppressor was in controlling weeds. Herbicides that have been able to restore weed growth include glyphosate (G3) at a dose of 0.750 l / ha, Methyl metsulfuron (M5) at a dose of 160 g / ha, A mixture of 240/10 SL (CG3) at a dose of 1.0 l / ha , Mixture B 360/10 SL (CB3) at a dose of 1.0 l / ha. A mixed herbicide A 240/10 SL with an LD50 value of 93.2 and a mixture of B 360/10 SL is 186.92 smaller than the LD50 value of a single glyphosate herbicide 186.83 and methyl metsulfuron 27.98. The index value of combination herbicide mixture A 240/10 SL is 1.0384 and herbicide mixture B 360/10 SL is 1.0262, thus the nature of the herbicide is not antagonistic.Keywords: Glyphosate, Methyl metsulfuron, LD50, Herbicide mixture.